Control Over Dimer Orientations on Vicinal Si(100) Surfaces in Hydrogen Ambient: Kinetics Versus Energetics. Issue 4 (27th November 2017) - Brückner, Sebastian; Supplie, Oliver; Dobrich, Anja; Kleinschmidt, Peter; Hannappel, Thomas
Abstract : In chemical vapor ambience, Si(100) surfaces and hydrogen are strongly interacting with each other at relevant process temperatures. Energetic considerations cannot solely describe step and terrace formation sufficiently, as the formation of equilibrium surface reconstructions can be counteracted by surface kinetics. In recent years, the combination of in situ reflection anisotropy spectroscopy (RAS) and complementary UHV‐based surface sensitive techniques helped to understand and control the entire Si(100) surface preparation, in particular step and domain formation, which strongly depend on the applied process conditions and surface misorientation. Here, we discuss vicinal, 6° misoriented Si(100) surfaces in comparison to results on larger terraces in order to derive a general view on how to promote either a kinetically or an energetically driven step formation. Dictated by the dominant driving force, monohydride Si(100) surfaces with "A‐type" (1 × 2) or "B‐type" (2 × 1) majority domain can be prepared, as we confirm with RAS as well as low energy electron diffraction, scanning tunneling microscopy and Fourier‐transform infrared spectroscopy. Well‐ordered DB double layer steps at the vicinal B‐type Si(100) surface cause a step‐related, derivative‐like RAS signal, in contrast to all other surfaces. In general, we confirm that high H2 pressures promote kinetically driven processes, while the impact of energetics increases with offcut magnitude. Abstract : Controlled preparation of the Si(100) surface in hydrogen‐based ambience is a key element for subsequent monolithic, low‐defect integration of III/V semiconductors by metalorganic vapor phase epitaxy. Here, optical in situ spectroscopy allows for controlling the entire preparation route of vicinal Si(100) surfaces. Combined with previous results on lower misorientations, the authors now give a conclusive picture how energetics and kinetics counteract and can be utilized to tune Si(100) surface formation.